Teaching Foreign Trade in English Through the Modalities Based on Competences and Using Moodle - Correa Díaz, Ana María (Profile: Issues in Teachers’ Professional Development, 2012)
With the new approach to guide the learning process of students with a model based on the development of competences, and in comparison with the traditional lecture-based learning, it is necessary to start working with the teaching modalities that help to achieve this objective. With that in mind, the aim of the study reported in this article was to show that through the use of active teaching methods focusing on the development of competences we can improve the writing, speaking and research competences in English of the students who nowadays take university subjects in a foreign language in Colombia. The results showed that the support provided by the platform promotes student motivation in carrying out their self-learning, which contributes to the development of the mentioned competences. Gracias al nuevo enfoque que guía el proceso de aprendizaje de los estudiantes a través de un modelo basado en el desarrollo de competencias, en comparación con el discurso expositivo tradicional, se hace necesario empezar a implementar un modelo de enseñanza basado en el desarrollo de competencias. Con esto en mente, el objetivo de la investigación que se reporta en este artículo fue demostrar que mediante el uso de métodos de enseñanza activa centrados en el desarrollo de competencias se pueden mejorar las habilidades de escritura, habla e investigación en inglés de estudiantes universitarios que actualmente cursan asignaturas en una lengua extranjera en Colombia. Los resultados del estudio muestran que en este proceso educativo la plataforma Moodle favorece la motivación de los estudiantes hacia la realización de su trabajo autónomo y el desarrollo de las mencionadas competencias.